Paul, Thessalonica, and early Christianity - Donfried, Karl P. (Grand Rapids, Michigan : William B. Eerdmans, 2002)
Originally published: London: T & T Clark, 2002. " Selection of fifteen essays written between 1974 and the present; they are offered here in their original form with the exception of minor corrections." -- P. vii.
Includes bibliographical references ( p. 305-331) and indexes.
Keywords: Bible. N.T. Thessalonians -- Criticism, interpretation, etc; Paul, the Apostle, Saint -- Theology; Church history -- Primitive and early church, ca. 30-600 -- Sources